Pemanfaatan Tumbuhan Obat Tradisional Masyarakat Desa Semata Kecamatan Tangaran Kabupaten Sambas - Ramdhayani, Annisa Nur; Syamswisna, Syamswisna; Fajri, Hayatul (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Information about plants used as traditional medicines is passed orally from generation to generation. Semata Village is one of the villages that still use plants in the process of traditional medicine. As the age grows, it is feared that public knowledge of plants as the basis for traditional medicine will decrease. Written documentation is necessary to be done by conducting ethnobotanical studies of medicinal plants. This study aimed to determine the types of plants used as the source of medicine by the community in Semata Village. The research was conducted using the descriptive method through interviews, observation, and identification of plants as the data collection techniques. The information was obtained from 43 informants consisting of shamans, massage therapists, and the community of Semata Village. The community of Semata Village used 60 species from 37 plant families that are believed to treat 44 types of disease symptoms. The dominant part of plants used is the leaves, while the plants that are often used come from the Zingiberaceae family. Kunyik Itam is the typical plant of Semata Village that is starting difficult to obtain. Rhizome of Kunyik ItamÂ  is used as medicine for asthma, cancer, and itching.